Dix Maitres Contemporains. - Galerie Isy Brachot, Bruxelles (Bruxelles : Galerie Isy Brachot, 1968)
Brandani ; Delvaux, Paul ; Ernst, Max ; Magritte, René ; Brauner ; Buffet ; Carzou ; Fini, Leonor ; Jansem ; Carzou ; Delmotte
Dix Maitres Contemporains, Galerie Isy Brachot, Bruxelles, du 28 juin au 31 aout 1968
boek